Variations of Subject–Verb Agreement Patterns in the Short Story Hänsel und Gretel in German and English: A Morphosyntactic Study - Safitri, Ayu; Hendrokumoro, Hendrokumoro (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study aims to identify and analyze variations in subject–verb agreement patterns in German and English through an examination of the short story Hänsel und Gretel. The study employs a qualitative contrastive analysis method based on the fairy tale. The analysis focuses on the number of subjects (singular and plural), the use of the past tense, copular verbs, and constructions with modal verbs. The findings reveal six main patterns that reflect the characteristics of each language. Some patterns show similarities, such as singular subjects in the past tense with third-person singular verb forms, as well as constructions with copular and modal verbs in the singular form. However, there are also significant differences, particularly in the use of verbs for plural subjects and plural modal verb constructions. These findings indicate that German has a more complex conjugation system compared to the simpler and more consistent English system. Therefore, the results can help language learners understand the structural differences between German and English and improve the accuracy of grammatical pattern usage in learning and communicationKeywords: Variation, Pattern Subject-Verb Agreement, Morphosyntax, Short Story